Domestic negotiations : gender, nation, and self-fashioning in US Mexicana and Chicana literature and art - McMahon, Marci R., 1975- (Rutgers University Press, 2013)
This book explores how U.S. Mexicana and Chicana authors and artists across different historical periods and regions, and how they use domestic space to actively claim their own histories. Drawing from a range of archival sources and cultural productions, the book demonstrates how the very sites of domesticity are used to engage with the many political and recurring debates about race, gender, and immigration affecting the lives of Mexicanas and Chicanas from the early twentieth century up through the twenty-first century.
Keywords: American literature -- Mexican American authors -- History and criticism.; American literature -- Women authors -- History and criticism.; Identity (Psychology) in literature.; Mexican Americans in literature.; Mexican American women in literature.; Mexican American arts.; Mexican American women artists.; Nationalism and literature -- United States -- History.; Littérature américaine -- Auteurs américains d'origine mexicaine -- Histoire et critique.; Écrits de femmes américains -- Histoire et critique.; Identité (Psychologie) dans la littérature.; Américains d'origine mexicaine dans la littérature.; Arts américains (mexicains); Femmes artistes américaines d'origine mexicaine.; Nationalisme et littérature -- États-Unis -- Histoire.; LITERARY CRITICISM -- American -- General.; SOCIAL SCIENCE -- Ethnic Studies -- Hispanic American Studies.; American literature -- Mexican American authors; American literature -- Women authors; Identity (Psychology) in literature; Mexican American arts; Mexican American women artists; Mexican American women in literature; Mexican Americans in literature; Nationalism and literature; United States; Criticism, interpretation, etc.; History